2011
DOI: 10.1111/j.1464-410x.2011.10340.x
|View full text |Cite
|
Sign up to set email alerts
|

Urethral trauma. Part II: Types of injury and their management

Abstract: What's known on the subject? and What does the study add? Iatrogenic trauma aside, urethral injuries are not common. Nonetheless, there have been a large number of cohort studies, generally of small numbers of patients.This review pulls together all of the information available to try and produce a coherent narrative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 111 publications
2
46
0
2
Order By: Relevance
“…A cadaveric study showed that the pubic bone and urogenital diaphragm are tightly adherent to the urethra proximal to the striated sphincter, but less adherent distal to the sphincter, resulting in a tendency toward urethral injury at the weaker, more distal point; that is, the bulbar urethra . In contrast to what is seen in adult patients, in children the site of injury tends to be more proximal, including the prostate and the bladder neck, and severe urethral disruption is more likely as a result of anatomical characteristics in children, including the fragile tissues of an immature pelvic structure, the relative intra‐abdominal position of the bladder and an immature prostate . Furthermore, unstable pelvic fractures, such as Malgaigne fractures and straddle fractures, are much more common in children, and the incidence of PFUI after these severe pelvic injuries is higher in children than in adults …”
Section: Pathophysiology and Mechanism Of Pfuimentioning
confidence: 99%
“…A cadaveric study showed that the pubic bone and urogenital diaphragm are tightly adherent to the urethra proximal to the striated sphincter, but less adherent distal to the sphincter, resulting in a tendency toward urethral injury at the weaker, more distal point; that is, the bulbar urethra . In contrast to what is seen in adult patients, in children the site of injury tends to be more proximal, including the prostate and the bladder neck, and severe urethral disruption is more likely as a result of anatomical characteristics in children, including the fragile tissues of an immature pelvic structure, the relative intra‐abdominal position of the bladder and an immature prostate . Furthermore, unstable pelvic fractures, such as Malgaigne fractures and straddle fractures, are much more common in children, and the incidence of PFUI after these severe pelvic injuries is higher in children than in adults …”
Section: Pathophysiology and Mechanism Of Pfuimentioning
confidence: 99%
“…2,10 Clinical features of urethral injury are listed in Table 1. With penetrating penile trauma, urological consultation is strongly advised, even for small lacerations and stab wounds, as surgical urethral closure may be required.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Except in cases of clearly superficial tangential injuries, a retrograde urethrogram (ordered during initial assessment by the ED physician) or direct cystoscopy (performed by the urologist during surgical exploration in the operating room) is routinely recommended for all penetrating penile injuries to evaluate for possible urethral injury. Both imaging modalities are recommended in urological trauma guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged attempts at realignment are discouraged, as they are likely associated with worse incontinence and erectile dysfunction. Patients who are successfully realigned require close follow-up as rate of future stenosis and obstruction approaches 80% 30 . In the setting of urethral injuries where primary realignment is not possible, delayed surgical repair is the recommended treatment.…”
Section: Urethral Traumamentioning
confidence: 99%